Scientist at School: Connecting Elementary Students to University Clinical Research Scientists Through Live Streams During a Pandemic in Southern Brazil (Principles and Practice of Clinical Research, 2021)
AbstractIntroduction: The social distancing generated by the COVID-19 pandemic had a great impact on education. Although very challenging to implement and adapt in an emergency scenario, distance learning opened novel opportunities to educational initiatives. The project Scientist at School, developed in southern Brazil during this period, had the goal to adapt postgraduate and elementary students’ encounters to a live stream format.Methods: This observational study analyzes the remote teaching process during the pandemic, with the project’s experience from different points of view. In addition to consulting the recorded access data from transmissions, three questionnaires answered by viewers evaluated content quality.Results: All live streams were classified as "excellent or good" by the students; with 66.7% of them affirming that the distance modality was not a limiting factor and that it could ease access to knowledge. Many of the organizers said that interacting with elementary school students and researchers from different fields helped them to expand their views on science production in the university and to improve their science communication skills. More than 85% of teachers and guests rated the activity as "excellent," however, one in two indicated that inequalities in internet access were a limitation for this learning modality.Conclusion: The project was able to provide a new experience of teaching and promoting science communication at a community level, exchanging knowledge in accessible language.Keywords: Distance learning, education, scientific communication, live stream, pandemic